ISOLATION AND CHARACTERIZATION OF PARTIAL CDNA OF SUCROSE SYNTHASE PUTATIVE GENE IN PALMYRA PALM (BORASSUS FLABELLIFER) - FAINMARINAT INABUY; Adi Pancoro (SEAMEO BIOTROP, 2010)
Intensification of biofuel resources is urgently needed considering the decrease in availability of world’s fossil fuel. Palmyra palm (Borassus flabellifer) is highly potential to be developed as bioethanol source regarding the high sucrose content in its nira. It was observed that nira produced in dry season is sweeter than that in rainy season, which presumed to be influenced by a difference in expression level of sucrose-related genes during the two seasons. Studies on Sucrose Synthase (SUS) gene of palmyra are therefore required prior to study the gene expression. Palmyra SUS gene sequence is currently unavailable in GenBank, thereby pair of primers was designed from highly conserved region of SUS proteins among monocots. A 1866 bp partial cDNA fragment of SUS putative gene has been succesfully isolated from RNA of the young leaves of B. flabellifer. BLASTn and BLASTp aligments showed that either BfSUS cDNA or BfSUS polypeptide has high similarity with SUS cDNA and proteins from diverse plant species, with the highest similarity shown by Tulipa gesneriana. The phylogenetic tree showed that SUS protein sequences of monocot species were distinctively grouped and splitted from those of dicot species. The BfSUS was clustered in monocot group, although not specifically grouped with particular monocot species. Nevertheless, B. flabellifer showed nearest genetic distance with Tulipa gesneriana and Oncidium cv.’Goldiana’. Characterization of BfSUS polypeptide using Geneious 4.6.2 indicated the presence of sucrose synthase (SUS) and glycosyl transferase (GT) domains, four putative UDP-glucose binding pockets within the GT domain, and a calcium-dependent Ser/Thr protein kinase binding site within the SUS domain. These domains and motifs are highly conserved in SUS proteins across plant species, hence confirming that the cDNA fragment obtained in this study is the putative gene of sucrose synthase of B. flabellifer. Keywords: Borassus flabellifer, nira, sucrose, sucrose synthase, SUS domain, GT domain,